Protein-lipid interactions stabilize the oligomeric state of BOR1p from saccharomyces cerevisiae - Pyle,E; Guo,C; Hofmann,T; Schmidt,C; Ribiero,O; Politis,A; Byrne,B (Analytical Chemistry, 2019)
The BOR proteins are integral membrane transporters which mediate efflux of boron. Structures of two BOR family members from Arabidopsis thaliana and Saccharomyces mikitiae indicate that the proteins exist as dimers. However, it remains unclear whether dimer formation is dependent on protein-lipid interactions or whether the dimer is the functional form of the protein. Here, we used the BOR1p protein from Saccharomyces cerevisiae (ScBOR1p), recombinantly expressed in its native host, to explore these aspects of BOR transporter structure and function. Native mass spectrometry (MS) revealed that ScBOR1p isolates as a monomer in a range of detergents. Lipidomics analysis showed that ScBOR1p co-isolates with phosphatidylserine (PS), phosphatidylcholine (PC), phosphatidylethanolamine (PE), and phosphatidylinositol (PI). Delipidation of ScBOR1p followed by addition of PS or PE causes formation of ScBOR1p dimers. Using a homology model of ScBOR1p, we identified a possible lipid binding site at the dimer interface comprising residues Arg265, Arg267, Arg480, and Arg481. A quadruple 4R/A mutant was expressed and isolated and also shown to be monomeric by native MS, and addition of PS or PE to this mutant did not reform the dimer. Functional complementation analysis revealed that the 4R/A mutant had boron efflux activity, suggesting that the ScBOR1p monomer is responsible for transport function. Taken together, these data strongly indicate that the physiological form of the ScBOR1p is the dimer and that dimer formation is dependent on association with membrane lipids.